A Cross-sectional Study on Breast Cancer among the Bangladeshi Female Population - Nasrin, Faria; Islam, Muhammad Rashedul; Mamun, Md Elias Al (Bangladesh Pharmaceutical Journal, 2022)
The goal of the study was to analyze Bangladeshi women's knowledge of breast cancer and attitudes toward breast self-examination (BSE) practice along with the participants' trust in the breast cancer treatment facility in Bangladesh. The cross-sectional study was carried out between March and July of 2021 among 268 Bangladeshi women over the age of 15 through Google form-based questionnaire who were asked 18 questions about breast cancer. The acquired data were analyzed using SPSS version 25 and Excel. The 88% of those surveyed had heard of breast cancer, and 63.4% were aware of its symptoms. Participants' overall knowledge of breast cancer was not satisfactory, with a mean knowledge score of 3.53 on a scale of 0 to 6, and 40.3% fell into the "good knowledge" category. Age, education, residence, and a family history of breast cancer were significant predictors of knowledge level. Only 53% had heard of BSE before, and only 29.5% admitted to being familiar with the BSE technique. Only 23.5% had previously conducted BSE. Only 11.2% of those polled had faith in Bangladesh's breast cancer treatment facilities. Based on the findings of this study, it can be assumed that the majority of women in Bangladesh have minimal understanding of breast cancer, the most common cancer among Bangladeshi women. It is high time to take the required steps to raise awareness about breast cancer and BSE. Furthermore, widespread access to mammograms, radiation, and oncology treatment should be ensured in an attempt to restore faith in healthcare facilities. Bangladesh Pharmaceutical Journal 25(1): 54-66, 2022 (January)